Association of serum components of the GH-IGFs-IGFBPs system with GHR-exon 3 polymorphism in normal and idiopathic short stature children - Ballerini, María Gabriela (2013)
Objective To investigate the possible association of circulating components of GH-IGFs-IGFBPs system with the GHR-exon 3 genotype in normal and idiopathic short stature (ISS) children. Design Descriptive, cross-sectional study in normal and ISS children. Subjects and methods 192 normal and 81 ISS children (age: 5–17 years) were included. Serum IGF-I, IGFBP3, ALS and GHBP levels were measured. GHR-exon 3 polymorphism (GHRd3) was analyzed by multiplex PCR assay. Normal and ISS children were divided according to GHR-exon 3 genotype: homozygous for the full-length GHR isoform (GHRfl) and carriers of one or two copies of the GHRd3 allele. Results GHRd3 genotype distribution (fl:fl/fl:d3/d3:d3,%) in normal (60:34:6) and ISS (64:32:4) was similar and reached Hardy–Weinberg equilibrium. ISS children had significantly reduced levels of GHBP and GH-dependent factors as compared to controls (p < 0.0001). Within the normal group, homozygous carriers of the GHRfl allele had significantly higher GHBP serum levels than those with one or two copies of the GHRd3 allele (Mean ± SEM; GHRfl: 3.2 ± 0.2 vs GHRd3: 2.7 ± 0.2 nmol/L, p = 0.04). No other significant association with GHR exon 3 polymorphism was found in either the normal or the ISS groups. Conclusions GHR exon 3 polymorphism is distributed similarly in normal and ISS children, however only normal homozygous children for GHRfl allele showed higher GHBP levels. The lack of association between GHBP and GHR polymorphism in ISS children might be related to the heterogeneity of this group, where potential defects in GH receptor action may result in partial GH insensitivity.